Graffiti Artist’s Historiographical Writing Model “Bansky” The Man Behind The Wall” in The Perspective of Johan Joachim Wincklemann - Suminto, RA Sekartaji; Carollina, Donna (Bina Nusantara University, 2023)
History writing can be understood as a way of writing, exposing, or reporting the results of historical research that has been carried out as a matter of embodiment of research reports or historical writing itself. Furthermore, historical writing became known as historiography. Before writing the historiography of graffiti artists in Indonesia, it is necessary to understand the writing model that has been done by previous historians, one of which is Johan Joachim Wincklemann. Thisarticle will use a book entitled